2015
DOI: 10.1371/journal.pone.0138895
|View full text |Cite
|
Sign up to set email alerts
|

No Outbreak of Vancomycin and Linezolid Resistance in Staphylococcal Pneumonia over a 10-Year Period

Abstract: BackgroundStaphylococci can cause wound infections and community- and nosocomial-acquired pneumonia, among a range of illnesses. Staphylococcus aureus and methicillin-resistant S. aureus (MRSA) have been rapidly increasing as a cause of infections worldwide in recent decades. Numerous reports indicate that S. aureus and MRSA are becoming resistant to many antibiotics, which makes them very dangerous. Therefore, this study retrospectively investigated the resistance to antimicrobial agents in all hospitalized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…Also, the European mean proportion of linezolid resistance among MRSA blood isolates included in this study was found to be very 1ow [0.29% (95% CI 0.21-0.40%)], attesting to the overall susceptibility of MRSA isolates to linezolid in Europe. This is also similar to local studies in Germany and Spain (Sierra et al, 2013;Yayan et al, 2015), Russia (Gostev et al, 2015), China (Huang et al, 2019), and Latin America (Vega and Dowzicky, 2017), but remarkably lower compared to results from Pakistan (48.1%) (Azhar et al, 2017) and India (2.8-7.0%) (Kaur and Chate, 2015;Kumar, 2016). In comparison to other multi-country surveillance studies, such as ZAAPS and SENTRY, linezolid activity against VREF and MRSA remains similarly very high (>98%) in Europe (Mendes et al, 2016;Deshpande et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Also, the European mean proportion of linezolid resistance among MRSA blood isolates included in this study was found to be very 1ow [0.29% (95% CI 0.21-0.40%)], attesting to the overall susceptibility of MRSA isolates to linezolid in Europe. This is also similar to local studies in Germany and Spain (Sierra et al, 2013;Yayan et al, 2015), Russia (Gostev et al, 2015), China (Huang et al, 2019), and Latin America (Vega and Dowzicky, 2017), but remarkably lower compared to results from Pakistan (48.1%) (Azhar et al, 2017) and India (2.8-7.0%) (Kaur and Chate, 2015;Kumar, 2016). In comparison to other multi-country surveillance studies, such as ZAAPS and SENTRY, linezolid activity against VREF and MRSA remains similarly very high (>98%) in Europe (Mendes et al, 2016;Deshpande et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…An exception is fluoroquinolones, e.g., ciprofloxacin (61), which is currently used due to its strong activity against Gram-negative bacteria in spite of its toxicity (62) and the increasing number of bacteria that are resistant to it (63). Remarkably, the diastereomer had activity comparable to that of ciprofloxacin, which was found to cause ϳ64%, 77%, and 98% killing of intracellular bacteria when tested under our conditions on infected ⌬F508-CFBE at 1 M, 5 M, and 15 M, respectively (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of clinical isolates of S. aureus have evolved to become resistant to commonly used antibiotics. The emergence of hospital-and community-associated methicillin-resistant S. aureus (MRSA) has worsened the situation further (1). Resistance has also been reported against both recently introduced and last-resort drugs used for treatment of S. aureus infection, such as vancomycin, daptomycin, and linezolid (2,3).…”
mentioning
confidence: 99%